Chemical and isotopic snow variability in East Antarctica along the 2001/02 ITASE traverse - Becagli S.; Proposito M.; Benassai S.; Flora O.; Genoni L.; Gragnani R.; Largiuni O.; Pili S. L.; Severi M.; STENNI, Barbara; Traversi R.; Udisti R.; et al. (2004)
As part of the International Trans-Antarctic Scientific Expedition (ITASE) project, a traverse was carried out from November 2001 to January 2002 through Terre Adelie, George V Land, Oates Land and northern Victoria Land, for a total length of about 1875 km. The research goal is to determine the latitudinal and longitudinal variability of physical, chemical and isotopic parameters along three transects: one west–east transect (WE), following the 2150m contour line (about 400km inland of the Adelie, George V and Oates coasts), and two north–south transects (inland Terre Adelie and Oates Coast–Talos Dome–Victoria Land). The intersection between the WE and Oates Coast–Victoria Land transects is in the Talos Dome area. Along the traverse, eight 2m deep snow pits were dug and sampled with a 2.5cm depth resolution. For spatial variability, 1m deep integrated samples were collected every 5 km (363 sampling sites). In the snow-pit stratigraphy, pronounced annual cycles, with summer maxima, were observed for nssSO42–, MSA, NO3– and H2O2. The seasonality of these chemical trace species was used in combination with stable-isotope stratigraphy to derive reliable and temporally representative snow-accumulation rates. The study of chemical, isotopic and accumulation-rate variability allowed the identification of a distribution pattern which is controlled not only by altitude and distance from the sea, but also by the complex circulation of air masses in the study area. In particular, although the Talos Dome area is almost equidistant from the Southern Ocean and the Ross Sea, local atmospheric circulation is such that the area is strongly affected only by the Ross Sea. Moreover, we observed a decrease in concentration of aerosol components in the central portion of the WE transect and in the southern portion of the Talos Dome transect; this decrease was linked to the higher stability of atmospheric pressure due to the channelling of katabatic winds.